2019
DOI: 10.1177/0040517519866938
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of soft composite reinforced with auxetic warp-knitted spacer fabric for stab resistance

Abstract: Auxetic warp-knitted spacer fabrics have gained increasing interest due to their excellent properties, such as shear resistance, indentation resistance, synclastic curvature and so on. Soft composites made from auxetic warp-knitted spacer fabrics and A/B two-component silicone rubbers were studied in this paper. The stabbing resistance of composites made by different auxetic fabrics (Fabrics 1–4#) and at different filling rates (0%, 20%, 40%, 70%, 100%), respectively, were tested using a universal Material Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Combining the measured values of NPR, conclusions can be drawn from Figure 8(a) that samples with higher NPR value can undergo larger impact load. This is because the samples with better auxetic performance would have denser face structure [31]; therefore, it could have better impact resistance. Energy absorption-deflection curve of composite (1#-4#) is shown in Figure 8(b).…”
Section: Low-velocity Impact Behavior Of Compositementioning
confidence: 99%
“…Combining the measured values of NPR, conclusions can be drawn from Figure 8(a) that samples with higher NPR value can undergo larger impact load. This is because the samples with better auxetic performance would have denser face structure [31]; therefore, it could have better impact resistance. Energy absorption-deflection curve of composite (1#-4#) is shown in Figure 8(b).…”
Section: Low-velocity Impact Behavior Of Compositementioning
confidence: 99%
“…In the literature, there are many studies on yarn [1,[9][10][11][12][13][14][15][16][17][18][19][20], woven fabric [21][22][23][24][25][26], knitted fabric [8,[27][28][29][30][31][32][33][34][35][36][37], composite [38][39][40][41] production related to low PR or auxetic textile materials. Auxetic fabrics can also be produced with auxetic yarns or conventional yarns.…”
Section: Introductionmentioning
confidence: 99%
“…Auxetic fabrics can also be produced with auxetic yarns or conventional yarns. Researchers changed the yarn properties and/or fabric patterns in literature to achieve low PR values [8,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. These studies show that the researchers used Re-entrant (zigzag), Rotating, Chiral, Fibril-Nodule, and Foldable mesh structures [2,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Auxetics, are unique materials with negative Poisson's ratio, which means that when stretched, they become thicker perpendicular to the applied force. Due to the specific behavior of auxetic materials under load, in a research by Xu et al (2020) it was revealed that these materials show enhanced properties such as impact resistance, indentation resistance, shear resistance, and energy absorption, compared to positive Poisson's ratio materials. Sun et al (2019) investigated the stab resistance property of auxetic weft knitted fabrics.…”
Section: Introductionmentioning
confidence: 99%